INITIATION AND MONITORING OF ANTISTEWARDSHIP PROGRAM IN 200 BEDDED HOSPITAL OF GIGIT BALTISTAN - Fatima, Safia; Khan, Ahmed Saeed; Fatima, Fozia (Pakistan Armed Forces Medical Journal, 2021)
Acautious and accountable administration of something assigned to one’s care is acknowledged as stewardship. Antimicrobial stewardship (AMS) term is basically functional in hospital setting as a tool for optimizing antimicrobial use. Stewardship had since been applied in the context of governance of the health sector as a whole, taking responsibility for the health and well-being of the population and guiding health systems at the national and global level. “Antibiotic stewardship programs can afford consistent updates on antibiotic prescribing, antibiotic resistance, and infectious disease management that address both national and local issues”. Sharing facility-specific information on antibiotic use is a tool to motivate improved prescribing, particularly if wide variations in the patterns of use exist among similar patient care locations. There were many possibilities for providing instruction on antibiotic consumption such as educational awareness that can be implemented in official and informal situations, messaging over and done with art works and brochures and news sheets or electronic communication to operate groups. Studying de-identified cases with providers where changes in antibiotic therapy could have been made is another useful approach. A practical implementation has been observed in 200 bedded hospitals of Gigit-Baltistan.